Development of 3D printed anthropomorphic radiotherapy head phantom using kinect® xbox 360® scanner - Zain, Nur Emirah Mohd (2021)
Radiotherapy aims to deliver a highly lethal radiation dose to cancer while preserving the healthy normal tissue. Pre-treatment quality assurance is extremely important to ensure accurate dose delivery and this is usually performed using standard phantom that is lacking in specific human anatomy. Therefore, the application of patient-specific phantom is important to avoid dosimetric errors during treatment. This study investigates the application of Kinect® Xbox 360® scanner to fabricate anthropomorphic radiotherapy head phantom using 3D printing technology. The use of a 3D scanner instead of computed tomography (CT) data to create the phantom is principally to avoid unnecessary radiation exposure, especially when collecting the superficial contour image of the patient. The development of the phantom in this thesis consists of two phases which are phantom fabrication and phantom evaluation. The phantom fabrication started by performing 3D scanning of standard RANDO® head phantom which to represent human head using Kinect® Xbox 360® scanner. The images obtained were edited in 3D format and transferred in stereolithography (STL) format for 3D printing. The phantom was printed using polylactic acid (PLA) materials with full infill. After the 3D printed head phantom was completely fabricated, the phantom was geometrically and dosimetrically evaluated in comparison to the RANDO® head phantom. The phantom size and weight were compared to the standard phantom and only a slight difference of grossly ± 18 % in size difference and 15% in weight difference were recorded. Hounsfield unit (HU) of both phantoms shows the value of ± 63.3 HU. The phantoms were later undergoing CT simulation and treatment planning was constructed with whole-brain target area using the Eclipse treatment planning system. The 3D printed head phantom, as well as RANDO® head phantom, was then irradiated as the constructed treatment planning with two types of dosimeters which were the TLDs and Gafchromic EBT3 films. The dosimetric results for GafChromic EBT3 films in the 3D printed head phantom did not show good results while acceptable gamma index analysis was obtained for RANDO® head phantom. The presence of the air gap in between the phantom slices is primarily the reason why the gamma analysis index cannot be completed for the 3D printed head phantom. The dose measurement using TLD produces almost similar results for both phantoms. Thereby, the 3D-Printed Head Phantom is successfully developed throughout the 3D scanning using a cheaper tool of Kinect® Xbox 360® scanner and the feasibility of the phantom in radiotherapy quality assurance is pragmatic with regards to the external shape of the head structure. The outcome from this study demonstrates the feasibility of a 3D printed phantom for radiotherapy application and with further optimization, the phantom might be customized with complex human anatomical features and superior dosimetric properties.